2014
DOI: 10.1186/1471-2407-14-692
|View full text |Cite
|
Sign up to set email alerts
|

Dual tracer evaluation of dynamic changes in intratumoral hypoxic and proliferative states after radiotherapy of human head and neck cancer xenografts using radiolabeled FMISO and FLT

Abstract: BackgroundRadiotherapy is an important treatment strategy for head and neck cancers. Tumor hypoxia and repopulation adversely affect the radiotherapy outcome. Accordingly, fractionated radiotherapy with dose escalation or altered fractionation schedule is used to prevent hypoxia and repopulation. 18F-fluoromisonidazole (FMISO) and 18F-fluorothymidine (FLT) are noninvasive markers for assessing tumor hypoxia and proliferation, respectively. Thus, we evaluated the dynamic changes in intratumoral hypoxic and prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Another possibility is that radiotherapy may increase the FMISO washout ratio in the same hypoxic cells. However, these possibilities are not likely, as Fatema et al reported that the intratumoral FMISO level did not show a significant decrease after a single course of radiation to hypoxic tumors in mice [35]. Another, more likely, cause is that the number of hypoxic cells decreases without significant changes in the uptake or washout ability of each hypoxic cell.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another possibility is that radiotherapy may increase the FMISO washout ratio in the same hypoxic cells. However, these possibilities are not likely, as Fatema et al reported that the intratumoral FMISO level did not show a significant decrease after a single course of radiation to hypoxic tumors in mice [35]. Another, more likely, cause is that the number of hypoxic cells decreases without significant changes in the uptake or washout ability of each hypoxic cell.…”
Section: Discussionmentioning
confidence: 93%
“…Dose escalation requires an accurate determination of the hypoxic area in order to properly target the hypoxia, and the current FMISO-PET might not have sufficient spatial resolution and contrast to delineate this area. In terms of spatial resolution, new PET scanners with higher spatial resolution would have the potential to more accurately demarcate the hypoxic area [35]. In addition, the new generation of hypoxic tracers with lower lipid solubility (e.g., 18 F-fluoroazomycin arabinoside (18 F-FAZA)) might enable the detection of hypoxia with higher contrast [36].…”
Section: Discussionmentioning
confidence: 99%
“…Despite such obvious expectation, a number of recent studies indicate that this is not the case. It has been shown by using 18 F-misonidazole (F-MISO) radioactive tracer and positron emission tomography (PET) to monitor the dynamic changes in intratumoral hypoxia that 10 and 20 Gy ablative dose irradiated human head and neck squamous cell carcinoma xenografts had minimal changes in the intratumoral hypoxia [ 76 ]. Our recent work with F-MISO has also demonstrated that there is no immediate increase in tumor hypoxia following 15 Gy ablative radiation [ 77 ].…”
Section: Factors To Consider Upon Combining Radiotherapy With Immunotmentioning
confidence: 99%
“…If pimonidazole can directly demonstrate the area of hypoxia, it could be direct evidence of hypoxia in the carcinogenesis process. On the other hand, there were a few studies that demonstrated the possibility of imaging monitoring in animal models using invasive needle or radioisotope in terms of hypoxia monitoring 32 , 33 . Recent interest in tumor hypoxic conditions has shifted to the area of diagnostic imaging due to the rapid development of diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%